Russian Journal of Genetics: Applied Research - Inge-Vechtomov, Sergei G.; Shumny, Vladimir K.; SpringerLink (Online service) (Moscow : Pleiades Publishing : Imprint: Pleiades Publishing.)
Russian Journal of Genetics: Applied Research contains translations of articles selected from Ekologicheskaya Genetika. The journal considers all aspects of ecological genetics including behavioral genetics, human ecological genetics, environmental and genetic toxicology, mutagenesis and carcinogenesis, simbiogenetics, aging, and genetic models in ecology. Russian Journal of Genetics: Applied Research is abstracted and/or indexed in: EMBASE, Google Scholar, OCLC, SCImago, SCOPUS, Summon by ProQuest.
Keywords: Human genetics; Human Genetics